Difficulties of Differentiating between Intellectual Property Rights and Human Rights on the Basis of the Case-Law Research Report ‘Internet: Case-Law of the European Court of Human Rights’ - ROZHKOVA, Marina Alexandrovna (Journal of Advanced Research in Law and Economics, 2016)
The article analyzes the problem of non-obvious difference between Human Rights and Intellectual Property Rights which often hinders their proper enforcement and protection. Methodological tools for the study are represented by a set of interrelated methods, techniques and methodologies. Elaboration depth of the posed scientific problem is provided, in particular, by such method of cognition as diachronic and synchronic comparison. The main idea of this article states that it is necessary to identify the demarcation line to distinguish between the abovementioned rights, which would enable proper implementation and protection of the rights of the parties concerned. Considering their high economic value and relation to the property issues, Intellectual Property Rights (as a part of economic rights) can be classified as ‘Property’, according to Art. 1 of Protocol No. 1 to the Convention on Human Rights and Fundamental Freedoms. However, moral rights, dealing with the realization of the creative potential and the personality of the Intellectual Property creator, are not recognized as ‘Property’ and are not protected by Art. 1 of Protocol No. 1 to the Convention on Human Rights and Fundamental Freedoms. In some cases, they can obtain protection under other provisions of the Convention (e.g. Article 10).
Keywords: intellectual property rights; economic rights; moral rights; property; human rights